Taxation of automation and artificial intelligence as a tool of labour policy - OOI, Vincent (Institutional Knowledge at Singapore Management University, 2019)
Rapid developments in automation technology pose a risk of mass displacement of human labour, resulting in the need to support and retrain displaced workers (a negative externality). We propose an “automation tax” that would slow the adoption of automation technology in appropriate circumstances, giving workers and social support systems time to adapt. This could be easily implemented through changes to the existing schedular system of depreciation/ capital allowances, reducing the uncertainty of its application and implementation costs. Such a system would be flexible enough to keep up with rapid technological developments. Two main dimensions may be adjusted to produce intended distortionary effects: 1) accelerated depreciation, and 2) bonus depreciation. While the benefits of efficiency gains mean that the automation tax is unlikely to have widespread application, it does provide a useful tool for specific situations where the rate of automation needs to be slowed due to its resultant social costs.